Community Empowerment of the "Teenager's Story House" through the establishment of a Youth Integrated Services Center in the Anggut Atas sub-district, Bengkulu City - Sumaryono, Dino; Linda, Linda; Darwis, Darwis; Ismiati, Ismiati; Marsofely, Reka Lagora; Mahayu, Hesti; Pramesti, Selvianita (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2024)
Adolescence is a transition period between childhood and adulthood. Discussions about adolescent health, especially reproductive health, are often held with friends of the same age. Therefore, the service team carried out service activities with the aim of forming a Youth Posyandu which has peer educators packaged through youth story house activities in Anggut Atas Village, Ratu Samban District, Bengkulu City. The activity method used is by conducting outreach and advocacy, training and establishing a youth posyandu with the advantage of a youth health story house. The result of this community service activity is that the village head determines youth representatives from each neighborhood to take part in a series of community service activities, namely a minimum of 2 people/neighborhood. Then all the administrators, namely the chairman, secretary and treasurer, expressed their willingness to become administrators of the Youth Posyandu and become peer educators on adolescent health in Anggut Atas Village. The implementation of peer educator training activities intended to increase teenagers' knowledge was carried out at the Anggut Atas Subdistrict Head's Office and was attended by teenagers who received socialization regarding youth posyandu and youth health story houses. The conclusion of this activity is that all evaluation indicators have been achieved, the potential of teenagers in Anggut Atas Village has been identified, a youth posyandu has been formed with the name "The integrated service post Healthy Fencing Teensat" with the advantage of a youth story house, and youth health peer educators have been trained who are ready to become advocates for youth problems in Anggut Atas Village.